2006
DOI: 10.1063/1.2345463
|View full text |Cite
|
Sign up to set email alerts
|

Complex dynamic behaviors of nonequilibrium atmospheric dielectric-barrier discharges

Abstract: . Complex dynamic behaviors of nonequilibrium atmospheric dielectric-barrier discharges.Journal of Applied Physics, 100 (6), article 063304, pp. 1-9.Additional Information:• In this paper, a one-dimensional fluid model is used to investigate complex dynamic behaviors of a nonequilibrium dielectric-barrier discharge ͑DBD͒ in atmospheric helium. By projecting its evolution trajectory in the three-dimensional phase space of gas voltage, discharge current density, and electrode-surface charge density, the atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 36 publications
1
28
0
4
Order By: Relevance
“…A detailed study of NDR in atmospheric DBD is reported elsewhere. 21 As reported previously, the existence of NDR indicates that the system may become chaotic under certain conditions. 11,12 We explore this by increasing the driving frequency.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…A detailed study of NDR in atmospheric DBD is reported elsewhere. 21 As reported previously, the existence of NDR indicates that the system may become chaotic under certain conditions. 11,12 We explore this by increasing the driving frequency.…”
mentioning
confidence: 85%
“…It is known that homogeneous atmospheric DBDs are characterized by one or multiple current pulses every half cycle of the applied voltage and the shape of the current pulses remains exactly the same from one cycle to another. 7,20,21 This most common discharge a͒ Author to whom correspondence should be addressed; electronic mail: wangdez@dlut.edu.cn mode can be obtained over a very wide range of the excitation frequency from our numerical simulation. Figure 1 shows the temporal evolution of the discharge current in a 4.0 kHz atmospheric DBD, together with the voltages.…”
mentioning
confidence: 99%
“…一般说来, 大气压等离子体可以用流体模型准确 地加以描述 [8,20] , 而细胞的描述则根据研究目的的不 同而有不同的描述形式, 要研究细胞中电场的分布与 演化, 多层细胞介电模型是比较合适的描述模型 [22] .…”
Section: 当等离子体作用于细胞时 外加电场与等离子体unclassified
“…实际上, 借助于细胞介电模型, 人们已经对不同给定 电压波形作用下细胞的跨膜电压等有了大量的研究结 果 [22] . 但是, 具体到介质阻挡放电条件下细胞内的电 [5,8,21] , 该模型在绝大 多数应用场景下也是适用的(当然需要电子能量分布 函数满足麦克斯韦分布) [29] , 特别是在大气压介质阻挡 放电中, 流体模型的有效性已经得到了大量实验的验 证, 有关流体模型的方程形式、离散化方法及数值求 解算法请参见文献 [7,20]. 在本文的计算条件下, 初始 [31,32] .…”
Section: 当等离子体作用于细胞时 外加电场与等离子体unclassified
“…The numerical scheme with very high computational efficiency can be found,19, 21 and the validation of this model has been assessed 9. To focus on the most essential plasma properties only pure helium without any impurities works as the background gas, the main chemical reactions in helium plasma are obtained from refs.,5, 22 and the impurity effects have been discussed in ref.…”
Section: Description Of Modelmentioning
confidence: 99%